Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1063/1.3267474
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nanoparticle charging on streamer development in transformer oil-based nanofluids

Abstract: Articles you may be interested inDielectric response of transformer oil based ferrofluid in low frequency range J. Appl. Phys. 114, 034313 (2013); 10.1063/1.4816012 Effect of nanoparticle polarization on relative permittivity of transformer oil-based nanofluids Iron oxide nanoparticles fabricated by electric explosion of wire: focus on magnetic nanofluids AIP Advances 2, 022154 (2012); 10.1063/1.4730405Effect of electron shallow trap on breakdown performance of transformer oil-based nanofluids Transformer oil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
205
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(223 citation statements)
references
References 25 publications
5
205
0
8
Order By: Relevance
“…10 An electron-scavenging model is proposed and generally used to explain these phenomena based on modeling the electrodynamic process in Fe 3 nanofluids. 8,9,11 Some researchers think the potential well generated by induced or polarized charges on the surface of nanoparticles can capture the passing electrons and enhance the breakdown performance of transformer oil. 10,12 In comparison with the dielectric breakdown strength of nanofluid, its prebreakdown streamer propagation behavior is more important to understand the fundamental modification effect of nanoparticle, which can give valuable insight into the events leading to breakdown.…”
mentioning
confidence: 99%
“…10 An electron-scavenging model is proposed and generally used to explain these phenomena based on modeling the electrodynamic process in Fe 3 nanofluids. 8,9,11 Some researchers think the potential well generated by induced or polarized charges on the surface of nanoparticles can capture the passing electrons and enhance the breakdown performance of transformer oil. 10,12 In comparison with the dielectric breakdown strength of nanofluid, its prebreakdown streamer propagation behavior is more important to understand the fundamental modification effect of nanoparticle, which can give valuable insight into the events leading to breakdown.…”
mentioning
confidence: 99%
“…Many studies showed that these ferrofluids withstand higher voltages than pure transformer oils, the property often presented as a paradox [3,4]. In this context, a theoretical modelling has indicated that nanoparticles in transformer oil can act as free charge scavengers which slow down the streamer velocity leading to dielectric breakdown [5]. Therefore, the mobility of SNP also plays an important role in reducing the streamer velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we proposed a full finite element approach where the charge transport equations of hydrodynamic diffusion-drift model and the electric field equation were numerically solved in a fully coupled system by using a standard finite element procedure for transient analysis [7][8][9][10][11]. Numerical technique for the hydrodynamic diffusiondrift modeling using charge transport equations is used in various applications such as corona discharge, heat transfer and cooling effect of heavy electric machines [12][13][14].…”
Section: Introductionmentioning
confidence: 99%